The Rural Integrated Community Clerkship: a vital stretch in the Alberta rural physician workforce pipeline - Nichols, Darren; Cockell, James; Lemoine, Daniel; Konkin, Jill (Canadian Medical Education Journal, 2023)
Background: Longitudinal integrated clerkships are thought to operate synergistically with factors such as rural background and practice intent to determine medical graduates’ practice types and locations—sometimes known as the pipeline effect. We examined the influence of the rural integrated community clerkship (ICC) at the University of Alberta on students choosing family medicine and rural practice. Methods: We completed a retrospective cohort analysis of graduates from 2009 - 2016. The cohort was cross-referenced by background, type of clerkship, practice type and practice location. We used χ2 analyses and risk ratios to measure the relative likelihood that ICC students would ultimately settle on rural practice and/or family medicine. Results: ICC participation had more influence than rural background on students’ choice of rural and/or family practice, and both factors were synergistic. Rotation-based clerkship students were least likely to enter family medicine or rural practice. Conclusions: The ICC is a clerkship model that influences students to become rural and/or family physicians, regardless of their rural/urban origins. The ICC diverts rural-interested students into rural practice and protects rural-origin students from ending up in urban practice. Expanding ICC infrastructure, including sustaining the rural physician workforce, will benefit rural Alberta communities by increasing the numbers of UA graduates in rural practice.